Physical and Chemical Characterization of Coffee Husk Ash Effect on Partial Replacement of Cement in Concrete Production - Koshe Hareru, Werku; Belayneh Asfaw, Firew; Ghebrab , Tewodros (International Journal of Sustainable Construction Engineering and Technology, 2022)
Today researchers all over the world are focusing on ways of utilizing either industrial or agricultural wastes as a source of raw materials for the construction industry. This is used to minimize the emission of CO2 during the manufacturing of cement. One of the agricultural waste products is coffee husk which is found in large amounts in Ethiopia. This paper aims to characterize the physical and chemical properties of Coffee Husks Ash (CHA) by using X-ray diffraction (XRD), Scanning electron microscope (SEM), and Fourier Transforms Infrared Spectroscopy (FTIR) tests, and also the experiment were conducted to determine the compressive, split tensile and flexural strength of the material and durability tests were determined. The result have shown that, when the replacement percent further increases, the crystalline material increases, silicate concentration decreases, and also the micro pores or air void are increases, which may lead to decreasing the strength of concrete. In the case of mechanical property of concrete, there has  been remarkable increment up to 5% CHA replacement and also strongly satisfied up to 10% replacement, furthermore increasing CHA replacement up to 20% are optimum dosage of normal concrete mix production of C-25 concrete. Finally, water absorption and sulfate attack of partially replaced concrete is shown as an improvement in the durability of concrete.